A proposed strategy for the optimal use of databases and statistical data collection tools to enhance the strategic plan of the Islamic University - Emara, Tarek Mahmoud; Ibrahim, Ehab Ibrahim Mohamed (Journal of Economic, Administrative and Legal Sciences, 2020)
The databases and data collection tools are a fundamental pillar of strategic planning, especially in the higher education sector. The Islamic University has been interested in achieving ambitious strategic plans and at the same time designing databases and data collection tools to support the decision- making process. So that, this study aimed at presenting a proposed strategy for the optimal use of databases and statistical data collection tools to enhance the strategic plan of the Islamic University. The importance of this strategy is that it plays an essential role in promoting the university's current strategic plan and at the same time it will be an appropriate tool for designing the future plans of the university. The study relied on the descriptive and analytical statistical approach as a framework for the applied and field study. where we designed a strategy supportive of the strategic plan of the Islamic University, and has developed a set of hypotheses associated with the vital role of databases to promote the basic plan the strategy of the Islamic University, the feasibility of the proposed strategy and its benefit, and the extent of satisfaction of the beneficiaries of this strategy, and that exists compatibility in rai of employees of the Islamic University and the views of employers on the proposed strategic plan. The result of study appeared that the average of the opinions of university employees and employers about the proposed strategy and its benefit. The study recommended the necessity of applying the proposed strategy while expanding the integration of databases and data collection tools within the strategic planning requirements of the university and there are need to develop existing databases or create new rules to meet the strategic planning requirements.
Keywords: strategic plan; optimal use; databases; opinion polls